Measurement of ψ (2S) polarisation in pp collisions at √s = 7 TeV - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (The European physical journal. C, Particles and fields, 2014)
The polarisation of prompt ψ (2S) mesons is measured by performing an angular analysis of ψ (2S)→μ+μ− decays using proton-proton collision data, corre-sponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb detector at a centre-of-mass energy of 7 TeV. The polarisation is measured in bins of transverse momentum pT and rapidity y in the kinematic region 3.5<pT<15 GeV/c and 2.0<y<4.5, and is compared to theoretical models. No significant polarisation is observed.
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, M. De Cian, A. Di Canto, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]
Gesehen am 14.10.2020
Im Titel ist "Psi" als griechischer Buchstabe dargestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol